Re-Assessment of PrP(Sc) Distribution in Sporadic and Variant CJD - Rubenstein, Richard (Public Library of Science, 2013)
Human prion diseases are fatal neurodegenerative disorders associated with an accumulation of PrP(Sc) in the central nervous system (CNS). Of the human prion diseases, sporadic Creutzfeldt-Jakob disease (sCJD), which has no known origin, is the most common form while variant CJD (vCJD) is an acquired human prion disease reported to differ from other human prion diseases in its neurological, neuropathological, and biochemical phenotype. Peripheral tissue involvement in prion disease, as judged by PrP(Sc) accumulation in the tonsil, spleen, and lymph node has been reported in vCJD as well as several animal models of prion diseases. However, this distribution of PrP(Sc) has not been consistently reported for sCJD. We reexamined CNS and non-CNS tissue distribution and levels of PrP(Sc) in both sCJD and vCJD. Using a sensitive immunoassay, termed SOFIA, we also assessed PrP(Sc) levels in human body fluids from sCJD as well as in vCJD-infected humanized transgenic mice (Tg666). Unexpectedly, the levels of PrP(Sc) in non-CNS human tissues (spleens, lymph nodes, tonsils) from both sCJD and vCJD did not differ significantly and, as expected, were several logs lower than in the brain. Using protein misfolding cyclic amplification (PMCA) followed by SOFIA, PrP(Sc) was detected in cerebrospinal fluid (CSF), but not in urine or blood, in sCJD patients. In addition, using PMCA and SOFIA, we demonstrated that blood from vCJD-infected Tg666 mice showing clinical disease contained prion disease-associated seeding activity although the data was not statistically significant likely due to the limited number of samples examined. These studies provide a comparison of PrP(Sc) in sCJD vs. vCJD as well as analysis of body fluids. Further, these studies also provide circumstantial evidence that in human prion diseases, as in the animal prion diseases, a direct comparison and intraspecies correlation cannot be made between the levels of PrP(Sc) and infectivity.